The eugenics movement and the eugenic idea in Britain 1900-1914: a historical study - Young, T. (1980)
This research falls into two parts. The first part begins with some observations on the methods employed in the writing of intellectual history. These observations are essentially critical and lead on to a detailed discussion of some proposed alternatives. The first chapter does not claim to have solved difficult theoretical and methodological problems but rather to have made possible greater clarity and awareness of what the problems are o In the light of these considerations an examination is then made of the relationship between Darwinian Biology and the major social doctxine claiming inspiration from it, namely~ Eugenics. With reference to this connection the central argument maintained is that there were systematic links between Darwinism and Eugenics o An attempt is made to analyse those links firstly by examination of certain theoretical features of Darwinism itself and secondly by an examination of the misreadings of Darwinism practised by Eugenics o This analysis is complemented by a detailed investigation of the structure of Eugenic thought as it appeared in Britain before the First World Waro The second part then extends this general picture by means of a number of case studies of Eugenic thinking and action on specific issues. The issues studied are those at the centre of controversy. during the period namely pauperism, alcoholism and mental deficiency. The priority in these case studies is the further development of the account of Eugenic thought but in each case there is an attempt, firstly to assess the impact of the Eugenic idea on public opinion and secondly, especially in the case of mental deficiency, to assess what legislative impact, if any, the Eugenic idea may have had